Effects of Dietary Lipid Levels on Growth Performance, Hematological Parameters, and Muscle Fatty Acid Composition of Juvenile Arapaima gigas - Carlos Andre Amaringo Cortegano; Luz Angélica Panaifo-García; Nidia Llapapasca; Nieves Sandoval; Adhemir Valera; Juan Rondón Espinoza; Gonzalo Orihuela; Andrea Carhuallanqui; Daphne D. Ramos-Delgado; Fred W. Chu-Koo; Ligia Uribe Gonçalves (Animals, 2025)
This study evaluates the effects of dietary lipid levels on growth performance, hematological health, and muscle composition of juvenile Arapaima gigas. We tested five isonitrogenous diets (451.7 g kg−1 of crude protein) with increasing lipid levels (6%, 10%, 14%, 18%, and 22%). A total of 600 juvenile A. gigas (80.0 ± 10.5 g; 21.8 ± 1.0 cm) were distributed into 20 tanks (500 L; n = 4; 30 fish per tank) in an indoor open system. The fish were fed to apparent satiety four times daily for 60 days. As dietary lipid levels increased, all growth parameters and lipid content in both the whole body and muscle declined. The diet containing 6% lipids resulted in the maximum final weight, weight gain, feed intake, and the lowest feed conversion rate. However, a maximum lipid level of up to 10.26%, with a gross energy-to-protein ratio of 10.15 kcal g−1 in the diet, as determined through polynomial regression analysis, can be used for juvenile A. gigas without significantly affecting weight gain. Diets with high lipid content (18% and 22% lipids) resulted in the lowest survival rates, highest feed conversion rates, lowest condition factor, visible skeletal protrusions, scale depigmentation, and impaired blood biochemistry. The content of eicosapentaenoic acid, docosahexaenoic acid, n-3, and the n-3:n-6 ratio increased in the muscle lipid fraction (mg g−1 of total lipids) in response to higher dietary lipid levels; however, this does not represent an overall improvement in the meat quality, since the total lipid content in the muscle (g of lipid per 100 g of muscle) was reduced due to impaired growth in fish fed high-lipid diets. Notably, the experimental diets also differed in fatty acid composition, which may have influenced some of the physiological and compositional responses observed. Diets with 6% lipids are recommended to provide optimal growth performance, and a maximum dietary lipid level of up to 10.26% is advised to ensure successful A. gigas farming without impairing weight gain.